Finding Your Balance: An Investigation of Recovery–Stress Balance in Vocational Dance Training. Issue 1 (2nd January 2020) - Blevins, Peta; Erskine, Shona; Hopper, Luke; Moyle, Gene
ABSTRACT: Professional dance careers require years of intensive training. Stress experienced during training must be balanced with adequate recovery to prevent overtraining and burnout. Little is known, however, about how dancers achieve recovery–stress balance. This study examined dancers' recollection of stress and recovery during their vocational dance training to identify potential stressors and recovery behaviors in vocational dance training. Twelve current and ex-professional ballet (n=4) and contemporary dancers (n=8) participated in the study. Four general dimensions, based on the extant overtraining literature in athletes, were identified: dance culture, intrapersonal, interpersonal, and situational factors. Cultural norms, health factors related to injury and illness, and transition periods within vocational dance training were sources of stress for participants. Dancers' responses to stress were categorized as adaptive or maladaptive. Maladaptive behavioral responses (e.g., ignoring injury, pain, and fatigue) were related to negative training outcomes associated with overtraining and burnout. Interventions that encourage adaptive behaviors for dance students to support health and well-being are recommended to address the recovery–stress balance in vocational dance training identified in this study.